Time in 85-100% heart rate zone increases lean body mass and VO2max in NCAA Division I soccer players - Cook, R. A.; Hastings, B.; Gottschall, J. S. (Journal of Fitness Research, 2014)
Introduction: Due to the growth and interest of women`s soccer in the past 20 years, multiple scientific studies have focused on how to enhance performance. Training status, defined as lean body mass and VO2max, is correlated to performance during games; specifically ground covered, number of sprints, and number of touches on the ball. Therefore, improving the training status of an athlete is a critical component of any soccer regimen. The purpose of the current study was to evaluate if a novel form of high intensity interval training (HIIT) could significantly improve training status during the 6-week offseason of an elite women`s soccer team. We hypothesised that time spent in the 85-100% heart rate zone would correlate with improvements in training status; specifically lean body mass and VO2max.